Binary metal sulfides and polypyrrole on vertically aligned carbon nanotube arrays/carbon fiber paper as high-performance electrodes. Issue 44 (16th September 2015) - Cai, Xiaoyi; Hansen, Reinack V.; Zhang, Lili; Li, Baosheng; Poh, Chee Kok; Lim, San Hua; Chen, Luwei; Yang, Jinglei; Lai, Linfei; Lin, Jianyi; Shen, Zexiang
Abstract : Rationally designed and coaxially grown Ni–Co–S and polypyrrole on vertically aligned carbon nanotube (VA-CNT) arrays/3D carbon fiber paper (CFP) are presented as novel freestanding electrodes for energy storage devices. Abstract : Pseudocapacitive materials, such as binary metal sulfides, show great promise as electrode candidates for energy storage devices due to their higher specific capacitance than that of mono-metal sulfides and binary metal oxides, but generally suffer from low energy densities when assembled in supercapacitor devices. To push the energy density limit of pseudocapacitive materials in devices, a new class of electrode materials with favorable architectures is strongly needed. Here, rationally designed and coaxially grown Ni–Co–S and polypyrrole on vertically aligned carbon nanotube (VA-CNT) arrays/3D carbon fiber paper (CFP) is presented as a novel freestanding electrode for energy storage devices. Our study has revealed that the catalyst preparation is the key step and the presence of an Al2 O3 buffer layer is essential for the growth of VA-CNTs. The 3D hierarchical VA-CNTs/CFP allows high areal loading and high utilization efficiency of the active materials. The binder-free asymmetric energy storage devices with Ni–Co–S/VA-CNTs/CFP as the positive electrode and polypyrrole/VA-CNTs/CFP as the negative electrode, respectively, demonstrate a high energy density of 82 W h kg −1 at 200 W kg −1 .